THE RELATIONSHIP BETWEEN STUDY SKILLS AND ACADEMIC ACHIEVEMENT AMONG ENGLISH MASTER’S STUDENTS - Attabik, Muhammad Haikal; Zainiza, Mailiza; Dewi, Anggraeni Khusuma (FKIP - Universitas Tanjungpura, 2026)
This study investigates the relationship between study skills and academic achievement among master’s students in English Language Education at Universitas Negeri Yogyakarta. Utilizing a quantitative correlational design, data were collected from 16 students through the Study Skills Assessment Questionnaire obtained from counseling services at the University of Houston-Clear Lake, which measured eight dimensions of study skills, including time management, concentration, note-taking, motivation, and writing. Students’ Grade Point Averages (GPA) were used as indicators of academic achievement. The data were analyzed using Pearson correlation via SPSS. The results revealed no statistically significant correlation between study skill dimensions and GPA, with all p-values exceeding 0.05. The strength of relationships (r-values) also remained very weak across all variables. Although writing and motivation showed the highest positive correlations, they were still insufficient to establish significance. These findings challenge previous literature that emphasizes the importance of study skills and suggest that academic success at the postgraduate level may depend more on intrinsic motivation, emotional well-being, self-regulation, and real-world learning strategies rather than mechanical study techniques. The study highlights the need for a more holistic approach in academic support programs for graduate students. Further research is recommended to include broader samples and consider additional psychological and contextual variables that influence academic outcomes.